Changes of Household Food Consumption in Indonesia: A Focus on Grain Consumption) - Saliem, Handewi P.; Harianto, Harianto; Jahroh, Siti (SOCA: Jurnal Sosial Ekonomi Pertanian; Vol. 10, No. 1 Februari 2010, 2010)
-